PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAKUL KARIMAH SISWA - Siti Ida Yanti (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This article aims to determine the development of students' good character at SDIT Al Muttaqin Kupang, to determine the implementation of the habit of reading the Qur'an before learning in developing students' character at SDIT Al Muttaqin Kupang, and to determine the supporting and inhibiting factors in the development of students' good character at SDIT Al Muttaqin Kupang. This research uses a qualitative approach with a case study type of research. Data collection techniques use observation, interviews, and documentation studies. The data analysis techniques used are data reduction, data display, and conclusion drawing. The results of this study show that 1) The development of good character at SDIT Al Muttaqin Kupang is running well and systematically with the active support of PAI teachers. Teachers not only deliver religious material formally, but also serve as role models and motivators for students' religious activities. 2) Efforts such as encouraging students to read the Qur'an, pray in congregation, review their memorization, and improve their recitation and memorization have proven to strengthen students' spiritual character. However, this success cannot be separated from the involvement of parents and the religious culture of the school. 3) A supporting factor in character building is the synergy between parents and the school. Conversely, obstacles arise from a lack of attention from the family and negative environmental influences. It is difficult to shape students' character if it is only nurtured at school without balanced control from the family and the surrounding environment.